THE IMPACT OF STUDENTS’ EDUCATIONAL STRESS ON THE DEVELOPMENT OF MIGRAINE AND METHODS OF ITS PREVENTION - Григорова, І. А.; Різниченко, О. К.; Щебетенко, В. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Presented results are based on questioning 4th year 87 studetns of Kharkiv National Medical University with the help of questionnaires specifically designed for identifying the signs of headache caused by migraine and the main triggers of the disease. Results of the study clearly demonstrate the presence of migraine signs in 28 respondents, 13 of them are female. Academic stress was found out to be the main factor that triggers headache (it was mentioned by all questioned students), additional triggers include ill-timed meals, sleep disorders, magnetic storms, allergies, premenstrual days for women, etc. Taking everything into account, we worked out the recommendations for prevention of academic stress so the development of migraine can be avoided.